Antioxidant Properties of Oral Antithrombotic Therapies in Atherosclerotic Disease and Atrial Fibrillation - Luigi Falco; Viviana Tessitore; Giovanni Ciccarelli; Marco Malvezzi; Antonello D'Andrea; Egidio Imbalzano; Paolo Golino; Vincenzo Russo (MDPI AG, 2023)
The thrombosis-related diseases are one of the leading causes of illness and death in the general population, and despite significant improvements in long-term survival due to remarkable advances in pharmacologic therapy, they continue to pose a tremendous burden on healthcare systems. The oxidative stress plays a role of pivotal importance in thrombosis pathophysiology. The anticoagulant and antiplatelet drugs commonly used in the management of thrombosis-related diseases show several pleiotropic effects, beyond the antithrombotic effects. The present review aims to describe the current evidence about the antioxidant effects of the oral antithrombotic therapies in patients with atherosclerotic disease and atrial fibrillation.